2016
DOI: 10.1016/j.jtcvs.2015.09.107
|View full text |Cite
|
Sign up to set email alerts
|

From bench to bedside: Can the improvements in left ventricular assist device design mitigate adverse events and increase survival?

Abstract: Patients with the new pump configuration showed a better freedom from cardiovascular death and lower incidence of fatal stroke and right ventricular failure. Further studies are needed to prove the favorable impact of pump-enhanced fluid dynamics on long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…There has been an increase in the number of patients being supported on continuous flow left ventricular assist devices (LVADs) over the past 7 years . While the transition to continuous flow devices has resulted in improved mechanical durability and patient survival, longer support duration has increased the incidence of device‐related adverse events . In the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) after 6 months of LVAD support, more than half the patients experienced a major adverse event .…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increase in the number of patients being supported on continuous flow left ventricular assist devices (LVADs) over the past 7 years . While the transition to continuous flow devices has resulted in improved mechanical durability and patient survival, longer support duration has increased the incidence of device‐related adverse events . In the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) after 6 months of LVAD support, more than half the patients experienced a major adverse event .…”
Section: Introductionmentioning
confidence: 99%
“…The two most innovative systems to avoid cable infections are: (1) the transcutaneous energy transmission (TET) system, which transfers energy via two coils, one under and the other over the skin; and (2) the Jarvik 2000 LVAD (Jarvik Heart Inc., NY), in which a retroauricular titanium pedestal is placed on the skull, thus providing a low infection rate [39,40]. The TET system was used in conjunction with the Arrow LionHeart (Arrow International, PA) as a pulsatile LVAD in an individual who survived for 3.5 years without skin complications [37].…”
Section: Discussionmentioning
confidence: 99%
“…Jarvik 2000 LVAD is a widely used device and it was originally conceived for left thoracotomy implantation on beating-heart through anastomosis onto the descending aorta. [9][10][11] Few reports are available regarding the clinical implications of LVAD--not only Jarvik 2000--outflow-graft anastomotic site and they mostly refer to single center experience with varying results. [12][13][14] However, no clinical studies have been reported to date for comparison of ascending versus descending aortic anastomosis in Jarvik 2000.…”
Section: Discussionmentioning
confidence: 99%